Euterpe oleracea mart. (açaí) reduces oxidative stress and improves energetic metabolism in myocardial ischemia-reperfusion injury in rats - Alegre, Patricia [UNESP]; Mathias, Livia [UNESP]; Lourenço, Maria Angelica [UNESP]; Dos Santos, Priscila Portugal [UNESP]; Gonçalves, Andrea [UNESP]; Fernandes, Ana Angélica [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Zornoff, Leonardo [UNESP]; Paiva, Sergio Alberto Rupp [UNESP]; Polegato, Bertha Furlan [UNESP] (My University, 2020)
Background: Euterpe oleracea Mart. (açaí) is a fruit with high antioxidant capacity and could be an adjuvant strategy to attenuate ischemia-reperfusion injury. Objective: To evaluate the influence of açaí in global ischemia-reperfusion model in rats. Methods: Wistar rats were assigned to 2 groups: Control (C: receiving standard chow; n = 9) and Açaí (A: receiving standard chow supplemented with 5% açaí; n = 10). After six weeks, the animals were subjected to the global ischemia-reperfusion protocol and an isolated heart study to evaluate left ventricular function. Level of significance adopted: 5%. Results: There was no difference between the groups in initial body weight, final body weight and daily feed intake. Group A presented lower lipid hydroperoxide myocardial concentration and higher catalase activity, superoxide dismutase and glutathione peroxidase than group C. We also observed increased myocardial activity of β-hydroxyacyl coenzyme-A dehydrogenase, pyruvate dehydrogenase, citrate synthase, complex I, complex II and ATP synthase in the A group as well as lower activity of the lactate dehydrogenase and phosphofructokinase enzymes. The systolic function was similar between the groups, and the A group presented poorer diastolic function than the C group. We did not observe any difference between the groups in relation to myocardial infarction area, total and phosphorylated NF-κB, total and acetylated FOXO1, SIRT1 and Nrf-2 protein expression. Conclusion: despite improving energy metabolism and attenuating oxidative stress, açai supplementation did not decrease the infarcted area or improve left ventricular function in the global ischemia-reperfusion model. (Arq Bras Cardiol. 2020; 114(1):78-86).
Euterpe Oleracea Mart. (Açaí) reduz o estresse oxidativo e melhora o metabolismo energético da lesão de isquemia-reperfusão miocárdica em ratos
Keywords: Chemical Reactions; Energy Metabolism; Euterpe Olerácea; Myocardial Ischemia; Myocardial Reperfusion Injury; Oxidative Stress; Rats